Wybrane elementy struktury listowej na podstawie korespondencji Czesława Miłosza z Jarosławem Iwaszkiewiczem - Zarębina, Maria (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The article analyses the private correspondence of Czesław Miłosz and Jarosław Iwaszkie- wicz that includes 86 letters from the years 1930-1980. The author concentrates on selected elements of the genre structure of letters, discussing the structure and the stylistic value of the initial and final formulae, i.e. dates, location, forms of address as well as submissions and signatures.